Possible Threats of IgA Vasculitis in Children: One Center Experience - Lanzbergaitė-Manuilova, Eglė; Rusonienė, Skirmantė; Jankauskienė, Augustina (Acta medica Lituanica, 2024)
Introduction: Immunoglobulin A vasculitis (IgAV) is the most common vasculitis in children. Although typically self-limiting, IgAV may result in serious complications. Our objective was to evaluate the incidence, clinical features, laboratory predictors and outcomes of IgA vasculitis with gastrointestinal (GI) and kidney involvement.Methods: Medical records of patients
Keywords: IgA vasculitis; gastrointestinal involvement; kidney involvement; laboratory predictors